2019
DOI: 10.1007/s00394-019-02092-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-ingestion of whey protein hydrolysate with milk minerals rich in calcium potently stimulates glucagon-like peptide-1 secretion: an RCT in healthy adults

Abstract: Purpose To examine whether calcium type and co-ingestion with protein alter gut hormone availability. Methods Healthy adults aged 26 ± 7 years (mean ± SD) completed three randomized, double-blind, crossover studies. In all studies, arterialized blood was sampled postprandially over 120 min to determine GLP-1, GIP and PYY responses, alongside appetite ratings, energy expenditure and blood pressure. In study 1 (n = 20), three treatments matched for total calcium content (1058 mg) were compared: calcium citrate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 40 publications
(65 reference statements)
1
28
0
Order By: Relevance
“…In a series of acute experiments, Chen et al ( 35 ) provided further evidence of a synergy between calcium and protein. In the first study, preloads (matched for calcium content—1000 mg) consisted of 4380 mg calcium citrate, 3745 mg milk minerals high in calcium, and 2050 mg milk minerals high in calcium with 50 g whey protein hydrolysate.…”
Section: Current Status Of Knowledgementioning
confidence: 97%
See 2 more Smart Citations
“…In a series of acute experiments, Chen et al ( 35 ) provided further evidence of a synergy between calcium and protein. In the first study, preloads (matched for calcium content—1000 mg) consisted of 4380 mg calcium citrate, 3745 mg milk minerals high in calcium, and 2050 mg milk minerals high in calcium with 50 g whey protein hydrolysate.…”
Section: Current Status Of Knowledgementioning
confidence: 97%
“…Previously, carbohydrate, fat, and protein ingestion, as well as SCFAs produced by the gut microbiota, have been found to independently stimulate GLP-1 release ( 31–33 ). Emerging evidence suggests that the synergy of protein and calcium could also act as a potent secretagogue of GLP-1 ( 34 , 35 ). In the most recent human study ( 35 ), this synergy produced some of the highest reported concentrations of GLP-1 following physiological ingestion to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, lower circulating glucagon-like peptide-1 may be a risk factor for type 2 diabetes (Lastya et al, 2014), thus if our data are showing a causal relationship, it could mean that those with a sweet tooth have lower type 2 diabetes risk, and this speculatively may be further enhanced by consuming a low sugar (non-sweet) breakfast. The magnitude of change was ~1.4 time higher, which is approximately half of what would be expected in the fasted to postprandial state (Chen et al, 2020). Despite the elevated glucagon-like peptide-1 concentration in those with a sweet tooth after PLAIN, insulin did not increase preto post-intervention.…”
Section: Resultsmentioning
confidence: 71%
“…As direct effects of GLP-1 on peripheral insulin sensitivity are unclear, the mechanism(s) by which GLP-1 may contribute to metabolic control are thought to also include microvascular recruitment and glucose-stimulated insulin secretion (Drucker 2018 ). Whilst enteral feeding pattern does not modulate the decline in peripheral insulin sensitivity during bed rest (Dirks et al 2019a ), other strategies that increase endogenous GLP-1 concentrations, such as enteral delivery mode (Luttikhold et al 2016 ) and/or nutrient composition (Gonzalez et al 2015 ; Gonzalez and Stevenson 2014b ; Chen et al 2019 ), warrant exploring as potential approaches to preserve GLP1 concentrations during bed rest.…”
Section: Discussionmentioning
confidence: 99%